(untitled) (Hershey, PA, 2007)
This book presents recent research efforts in Artificial Intelligence about building artificial systems capable of performing cognitive tasks. A fundamental issue addressed in this book is if these cognitive processes can have any meaningfulness to the artificial system being built"--Provided by publisher
Keywords: Artificial intelligence,Cognitive science,Artificial Intelligence,Cognition,Trí tuệ nhân tạo,Khoa học nhận thức; Research,Research,Nghiên cứu,Nghiên cứu